Shifting corporate geographies in global cities of the South: Mexico City and Johannesburg as case studies - Parnreiter, Christof; Oßenbrügge, Jürgen; Haferburg, Christoph (DIE ERDE – Journal of the Geographical Society of Berlin, 2013)
Global city research links the expansion of advanced producer services in major cities to the internationalisation of real estate markets as well as to the spread of (mainly) high-rise office complexes. This research, however, has based its findings mainly on cases of the Global North. This paper examines, based on Grant and Nijman’s (2002) suggestion that the “internal spatial organisation of gateway cities in the less-developed world” reflects “the city’s role in the global political economy”, which patterns occur in two metropoles of the Global South. In addition to this, the analysis focuses especially on the driving forces behind the changes in corporate geographies. The analysis is placed in Mexico City and Johannesburg and based on real estate market data (offices) as well as background documents on urban development. The outcome shows that in these cities, local transformation processes of the real estate market and office space location are indeed considerably shaped by global market dynamics. However, the findings also indicate that there is no clear scale dependence of the territorial form. In order to comprehensively understand the changes in the corporate geographies therefore, it is necessary to direct more attention to local and national dynamics. The restructuring of the built environment in both cities can only be grasped fully by considering the particular role of local and national governments. This additional entry point to an understanding of shifting corporate geographies helps to put recent dynamics of global capitalism and politics of urban neoliberalism in perspective.